Junshanyinzhen tea extract prevents obesity by regulating gut microbiota and metabolic endotoxemia in high-fat diet fed rats - Jian Ouyang; Xiuping Li; Changwei Liu; Danmin Lu; Jie Ouyang; Fang Zhou; Qi Liu; Jianan Huang; Zhonghua Liu (Food Science and Human Wellness)
Obesity is associated with gut dysbiosis and metabolic endotoxin. Junshanyinzhen tea extract (JSTE) reduced fat accumulation and body weight in obese mice. However, the effects and mechanism of JSTE in preventing obesity were unclear. Therefore, we used different doses of JSTE (75, 150 and 300 mg/(kg·day)) to evaluate the effect on high-fat diet (HFD) -induced rats under 8 weeks of intervention. Here, our results showed that JSTE could significantly reduce body weight gain, blood lipid levels and fat accumulation, improve fatty damage in liver tissue (P < 0.05). In addition, JSTE increased the expression of intestinal tight junction proteins (P < 0.05), relieved metabolic endotoxemia (P < 0.05) and chronic low- grade inflammation in HFD rats. Sequencing of fecal samples showed that JSTE could effectively reverse the microbial diversity and the ratio of Firmicutes to Bacteroidetes to normal levels in HFD- fed rats. Desulfovibrioceae and Erysipelotrichaceae, which are positively related to obesity, were decreased by JSTE intervention (P < 0.05). while Bifidobacteriaceae, Bacteroidaceae, Akkermansia, and Clostridium, which are negatively related to obesity, were increased. Together, these results suggested that JSTE might effectively prevent obesity by modulating gut microbiota dysbiosis, intestinal barrier dysfunction, metabolic endotoxemia and chronic low-grade inflammation in HFD-induced rats.